Forms, folds and sizes : all the details graphic designers need to know but can never find. - Evans, Poppy, ....- (Gloucester : Rockport, 2004)
Completely practical, with only the most needed information, this title provides designers with all the little details that can make or break a design, such as how much space to leave in the gutter when designing barrel folds, how to layout a template for a box and the ratios for each part, metric conversion charts, standard envelope sizes in the USA, Europe, Canada and Asia.
Keywords: Verpakkingen